EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DENGAN GUIDE NOTE TAKING (GNT) PADA MATERI BANGUN RUANG SISI DATAR DITINJAU DARI KEMAMPUAN PENALARAN SISWA KELAS VIII SMP NEGERI DI KOTA SURAKARTA TAHUN AJARAN 2013 / 2014 - Ajeng Novalin Wija Pratiwi; Budiyono Budiyono; Imam Sujadi (Jurnal Pembelajaran Matematika, 2015)
Abstract : The study aimed to know: 1) which learning model of the cooperative learning model of the Jigsaw-GNT, the cooperative learning model of the Jigsaw, and the direct learning model results in a better learning achievement in Mathematics; (2) which students of the students with the high reasoning ability, the students with the moderate reasoning ability, and the students with the low reasoning ability have a better learning achievement in Mathematics; (4) in each category of the reasoning abilities, which learning model of the cooperative learning model of the Jigsaw-GNT, the cooperative learning model of the Jigsaw, and the direct learning model results in a better learning achievement in Mathematics; and (3) in each learning model, which students of the students with the high reasoning ability, the students with the moderate reasoning ability, and the students with the low reasoning ability have a better learning achievement in Mathematics. This study was a quasi-experimental study with a 3 x 3 factorial design. The study population was all of grade VIII students of Junior High School in Surakarta. Sampling was done by stratified cluster random sampling. The instruments employed to gather the data of the research were test of learning achievement in Mathematics and test of reasoning ability. The data were analyzed using unbalanced two ways ANOVA. From the analysis, it was concluded as follows 1) The cooperative learning of Jigsaw-GNT have a better learning achievement in Mathematics than those instructed with the cooperative learning model of the Jigsaw and those instructed with the direct learning model; the cooperative learning model of the Jigsaw high results in a better learning achievement in Mathematics than the direct learning model, 2) The students with the reasoning ability is better than that of the students with the moderate reasoning ability and that of the students with the low reasoning ability; the students with the moderate reasoning ability have the same good learning achievement in Mathematics as those with the low reasoning ability, 4) In each category of the reasoning abilities, the students instructed with the cooperative learning model of the Jigsaw-GNT have a better learning achievement in Mathematics than those instructed with the cooperative learning model of the Jigsaw and those instructed with the direct learning model, and the students instructed with the cooperative learning model of the Jigsaw have a better learning achievement in Mathematics than those instructed with the direct learning model, 3) In each learning model, the learning achievement in Mathematics of the students with the high reasoning ability is better than that of the students with the moderate reasoning ability and that of the students with the low reasoning ability, and the learning achievement in Mathematics of the students with the moderate reasoning ability is the same as that of the students with the low reasoning ability.Keywords: Jigsaw, Guided Note Taking (GNT), direct learning, reasoning ability, and learning achievement in Mathematics.